Kennett, G. I., - The American Soldier In World War II - McGuire, Phillip (Teaching History: A Journal of Methods, 1998)
Lee Kennett’s book is a new paperback edition of a book originally published in 1987. With information from new sources, the author has produced a first rate social history of the American G.I. during World War II. He has detailed the "collective portrait" and the "collective experience" of the G.I. from his draft and induction to his return to civilian life. In doing so, Kennett based his story primarily on the noncombatant experiences of the G.I., the letters and memoirs of the G.l.s themselves, the thoughts of their commanding officers, the statements of fellow Allies and enemies, those who were liberated and conquered, and the historical literature of the Second World War.